Mechanized recovery of olive pruning residues: ash contamination and harvesting losses - A. Assirelli; A. Acampora; S. Croce; R. Spinelli; E. Santangelo; L. Pari (Journal of Agricultural Engineering, 2013)
Agricultural residues represent an important source of biomass for energy. Among the available biomass suitable for energy and available in Italy, pruning represents about the 20% of the total. About 1.184 million of hectares are planted with olive trees; the pruning residues coming from these plantations represent a wide source of biomass at National level. The authors tested six commercial pruning harvesters to determine harvesting losses and product contamination when recovering pruning residues. All harvesters used a mechanical pick-up to collect the residues and a shredder to reduce them into chips. Three different pick-up settings were tested and namely: 1 cm above ground level, manufacturer’s specification and 3 cm above ground level. Ash content in the shredded material was taken as a measure of contamination: the uncontaminated branch material collected directly from the trees had a value of 3.5%, whereas in shredded residues varied between 4.5% and over 5.5%, for the shortest and the longest distance between the pick-up and the soil surface, respectively. Harvesting losses were slightly, but significantly, related to pick-up setting, and mainly depended on machine type. Both machines have shown a good quality of the work performed and the results obtained indicates that the work phases could be simplified in order to reduce both the time of use and the harvesting costs.